Colonial Legacies Economic and Social Development in East and Southeast Asia - Booth, Anne E. (University of Hawai'i Press, 2007)
Taiwan and South Korea, both former Japanese colonies, achieved rapid growth and industrialization after 1960. The performance of former European and American colonies (Malaysia, Singapore, Burma, Vietnam, Laos, Cambodia, Indonesia, and the Philippines) has been less impressive. Some scholars have attributed the difference to better infrastructure and greater access to education in Japan's colonies. Anne Booth examines and critiques such arguments in this ambitious comparative study of economic development in East and Southeast Asia from the beginning of the twentieth century until the 1960s. Lucidly and accessibly written, 'Colonial Legacies' offers a balanced and elegantly nuanced exploration of a complex historical reality. It will be a lasting contribution to scholarship on the modern economic history of East and Southeast Asia and of special interest to those concerned with the dynamics of development and the history of colonial regimes.